A STUDY ON CHILD CARE AND PROTECTION: WELFARE TO NATION - Chandra Dalai, Krushna (International Journal of Psychosocial Rehabilitation, 2021)
The significance and the importance of the child lie in the fact that the child is the best creature of universe. If there was no child, there would be no humanity and there cannot he universe without humanity. Therefore, mankind owes to the child the best that it has to be given. "International concern for the Protection of Rights of the Child”, If there is no proper growth the child today, the future of the country will be dark. The Quality of the life they enjoy today would ultimately determine the quality of future population. Hence children are precious lot. Very often we ignore the children and hence lose an opportunity to make valuable citizen to the future generation. If a child goes wrong for want of proper attention, training and guidance it will indeed be deficiency of the society. Children need special protection because of their tender age, physique and mental facilities. They are an important national asset and the future well being of the nation depends on their personal growth. They need special law to protect them from exploitation and fraud to save them from certain liabilities and develop their personality in view of their weak position. It is not an exaggeration to say that the children are the blooming flowers of garden of Society and so, it is our duty to protect these flowers from damaging effects of excessive exposure to heat, cold and rain. The author tried his best explore all core aspects in this paper.